Analisis Peningkatan Motivasi Belajar Mahasiswa Melalui Pendekatan Berpusat Pada Siswa - Nini Carlina Lase; Anisetus Elvin Halawa (CV. SINAR HOWUHOWU, 2024)
This study aims to enhance college students' learning motivation through a student-centered learning approach. In higher education settings, learning motivation plays a crucial role in students' academic success. This research employs survey and interview methods to collect data on learning motivation before and after the implementation of the student-centered approach. The results indicate a significant increase in learning motivation among students who actively engage in the learning process. This conclusion suggests that a student-centered approach effectively fosters engagement and learning motivation. Recommendations for further development of this approach are also provided as guidance for future educators.